Optic disc pit with maculopathy – a case report - Olszewski, Mateusz; Marczak, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
The article presents a case of an 18-year old man with bilateral optic disc pit associated with serous macular detachment in the left eye. Optic disc pit is a rare congenital abnormality of the optic nerve head, which affects 1:11 000 people, with no gender predilection. Optic disc pits are usually incidental findings on fundus examination. In ophthalmic examination, optic disc pit presents as an oval, gray, white or yellowish depression in the optic disc, commonly involving temporal quadrants, but may be situated in any sector. Approximately 25–75% of eyes with optic disc pits have a poor visual prognosis, as a result of serous macular detachment and macular holes. There are no guidelines on the management of patients with optic disc pit maculopathy. Numerous techniques have been described, including laser photocoagulation, intravitreal gas injection and pars plana vitrectomy with many different modifications.